2023
DOI: 10.1029/2023gc010982
|View full text |Cite
|
Sign up to set email alerts
|

Active Deformation Constraints on the Nubia‐Somalia Plate Boundary Through Heterogenous Lithosphere of the Turkana Depression

M. Musila,
C. J. Ebinger,
I. D. Bastow
et al.

Abstract: The role of lithospheric heterogeneities, presence or absence of melt, local and regional stresses, and gravitational potential energy in strain localization in continental rifts remains debated. We use new seismic and geodetic data to identify the location and orientation of the modern Nubia‐Somalia plate boundary in the 300‐km‐wide zone between the southern Main Ethiopian Rift (MER) and Eastern Rift (ER) across the Mesozoic Anza rift in the Turkana Depression. This region exhibits lithospheric heterogeneity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
(265 reference statements)
1
1
0
Order By: Relevance
“…A relatively small uplift is observed beneath the GP, which is located west of the SMER and north of the Chamo Basin that extends south toward the Kenyan Rift. A comparison of results from earlier work (Braile et al, 1994;Kounoudis et al, 2023;Musila et al, 2023;Ogden et al, 2023;Sippel et al, 2017) with the one from this work showed that the EARs south of the MER are in an advanced stage of the rifting process than the SMER. Bonini et al (2005) also indicated that extensional structures started to develop in the Southern MER due to the northward propagation of Kenya Rift-related deformation.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…A relatively small uplift is observed beneath the GP, which is located west of the SMER and north of the Chamo Basin that extends south toward the Kenyan Rift. A comparison of results from earlier work (Braile et al, 1994;Kounoudis et al, 2023;Musila et al, 2023;Ogden et al, 2023;Sippel et al, 2017) with the one from this work showed that the EARs south of the MER are in an advanced stage of the rifting process than the SMER. Bonini et al (2005) also indicated that extensional structures started to develop in the Southern MER due to the northward propagation of Kenya Rift-related deformation.…”
Section: Resultssupporting
confidence: 50%
“…The Chew Bahir basin, located at the southern end of the GP is considered to be the northernmost propagation of the Kenya Rift, which accommodates extensional deformation south of the Gofa Basin and Range (Corti, 2009 & reference therein). A belt of seismically fast velocity mantle lithosphere that forms the linking zone between the MER and EAR is usually associated with diffused crustal deformation and lacks recent magmatism (Musila et al, 2023). On the other hand, seismically slow velocity mantle lithosphere and recent magmatism in the linkage zone are characterized by localized crustal strain, which is driven by lithospheric heterogeneity.…”
Section: Tectonicsmentioning
confidence: 99%